Analyzing the phenomenon of unemployment in Iraq: the legacy of the past, manifestations of the present, and solutions strategies - Hussein ali abd ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
The Iraqi economy suffers from the problem of unemployment significantly, a problem whose effects go beyond the economic dimension, as it is linked to the social, security and health dimension. It hasbecome a necessity to reduce this phenomenon and find effective solutions to it, especially in the conditions of the Iraqieconomy, which suffers from many economic problems that accompanied this problem. Due to the drop in oil prices in global markets in an economy that depends heavily on the revenues of the oil sector, the problem of unemployment in the economy has deepened to high levels, and it has motivated unemployed youth to stage protests and demonstrations to find solutions that eliminate this problem.DOI /10.54633/2333-021-042-017